2022
DOI: 10.3390/cells11111817
|View full text |Cite
|
Sign up to set email alerts
|

Blocking Metabotropic Glutamate Receptor Subtype 7 via the Venus Flytrap Domain Promotes a Chronic Stress-Resilient Phenotype in Mice

Abstract: Chronic psychosocial stress participates prominently in the etiology of various psychiatric conditions and comorbid somatic pathologies; however, suitable pharmacotherapy of these disorders is still of high medical need. During the last few decades, research on mGlu receptors advanced remarkably and much attention was given to the mGlu7 subtype. Here, genetic mGlu7 ablation, short-term pharmacological mGlu7 blockade, as well as siRNA-mediated knockdown of mGlu7 were shown to result in an acute anti-stress, ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…Docking in the third orientation along the α6 helix looked promising (Figure 14). As for option 2, molecular characteristics of this docking are in agreement with the SAR data: (1) H-bonds with S160 and S229, (2) hydrophobic contacts with A183, P184, K233 in an out-of-plane conformation, (3) halogen bonds 35 with S237, Q240, (4) a restricted environment around the iodophenyl, (5) mGlu7 selectivity because of K233 and S237 interactions. The complex remained stable in a 5 ns molecular dynamics simulation.…”
Section: Molecular Modeling For Xap044 Binding Modesupporting
confidence: 72%
See 1 more Smart Citation
“…Docking in the third orientation along the α6 helix looked promising (Figure 14). As for option 2, molecular characteristics of this docking are in agreement with the SAR data: (1) H-bonds with S160 and S229, (2) hydrophobic contacts with A183, P184, K233 in an out-of-plane conformation, (3) halogen bonds 35 with S237, Q240, (4) a restricted environment around the iodophenyl, (5) mGlu7 selectivity because of K233 and S237 interactions. The complex remained stable in a 5 ns molecular dynamics simulation.…”
Section: Molecular Modeling For Xap044 Binding Modesupporting
confidence: 72%
“…The discovery of mGlu7 homodimer ligands has been hampered by its difficult activation, despite its value as a therapeutic target in several CNS diseases. , Yet, screening campaigns have yielded some allosteric modulators, including XAP044 discovered by scientists at Novartis . They showed that XAP044 is an mGlu7 receptor antagonist with the particularity that it does not bind to the receptor transmembrane domain as most other mGluR modulators but to the extracellular domain.…”
Section: Discussionmentioning
confidence: 99%